2010
DOI: 10.1371/journal.pone.0012371
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Heme Oxygenase-1 Concentration Is Elevated in Individuals with Type 2 Diabetes Mellitus

Abstract: BackgroundCirculating concentrations of heme oxygenase-1 (HO-1) have been recently reported to be elevated in several chronic disorders. However, no study has ever examined the association between circulating HO-1 concentrations and type 2 diabetes mellitus (T2DM).Methods and Findings581 cases with newly-diagnosed T2DM (New-T2DM) and 611 comparison controls were recruited in this two-phase case-control study, comprising 420 cases and 429 controls collected in the first phase study and 161 cases and 182 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 31 publications
7
71
2
4
Order By: Relevance
“…Recent studies have shown elevated plasma levels in several chronic disorders, like Parkinson's disease and hemophagocytic syndrome, and in newly diagnosed type 2 diabetics (49-51). Until today, the sources of circulating HO-1 are unknown and it is postulated that plasma HO-1 is due to "leakage" of the enzyme from tissues to the plasma compartment (49,52). Here, we demonstrate that HO-1 is an adipokine expressed and released by human primary adipocytes in a differentiation-dependent manner and that circulating levels of HO-1 are increased in obese men, correlating with the size of subcutaneous adipocytes.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have shown elevated plasma levels in several chronic disorders, like Parkinson's disease and hemophagocytic syndrome, and in newly diagnosed type 2 diabetics (49-51). Until today, the sources of circulating HO-1 are unknown and it is postulated that plasma HO-1 is due to "leakage" of the enzyme from tissues to the plasma compartment (49,52). Here, we demonstrate that HO-1 is an adipokine expressed and released by human primary adipocytes in a differentiation-dependent manner and that circulating levels of HO-1 are increased in obese men, correlating with the size of subcutaneous adipocytes.…”
Section: Discussionmentioning
confidence: 57%
“…For example, Bao et al 26 found slightly increased plasma HO-1 concentrations in patients with newly diagnosed type II diabetes (2.4 ng/ml), compared with controls (1.1 ng/ml). This was felt to reflect the effects of hyperglycemia, a known pro-oxidant state.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both iron and carbon monoxide are products of HO-1 activity, it is likely that they coexist in various micromolar concentrations in conditions such as cancer [27][28][29][30][31], diabetes mellitus [21], rheumatoid arthritis [22], and mechanical circulatory support [18,26]. Although it is not possible to directly extrapolate our findings as the underpinning of hypercoagulability in these various settings [18,22,[26][27][28][29][30][31], it is possible that exposure of circulating fibrinogen to various combinations of iron and carbon monoxide may be enhancing coagulation in these disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytically released iron may also contribute to hydroxyl radical modification of fibrinogen [19] or bind directly to fibrinogen [20] as recently demonstrated. HO-1 activity is also increased systemically in inflammatory disorders associated with thrombophilia, such as diabetes mellitus [21] and rheumatoid arthritis [22]. Critically, SEM-based investigations demonstrated that the fibrin matrix formed from blood obtained from individuals with diabetes mellitus [23] or rheumatoid arthritis [24] was very similar to that observed when normal blood was exposed to ferric chloride [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 95%